Effects of Lidocaine Concentration on Streptococcus Mutans Bacteria - Muhammad Wildan Hari Subagya Haryono; Poerwati Soetji Rahajoe (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
Lidocaine is one of the local anesthetics agents that are frequently used in dentistry. Streptococcus mutan is a gram-positive, facultatively an aerobic bacterium commonly found in human oral cavity. The study aims to find out the effects of Lidocaine concentration against Streptococcus mutans bacteria. The study used experimental design with liquid and solid dilution method to find out bacteriostatic and bacteriocidal effects of Lidocaine concentration. The test bacteria used in the study are the ones, which have been compared with Mcfarland standard solution with 10μCFU/ML concentration. The Lidocaine concentrations were 2%, 1%,0.5%, 0.25%, 0.125%, 0.0625%, 0.03125%, 0.015625%, and 0.007812%. Kruskal-Wallis and Mann-Whitney methods were used for the statistical test. The result of the study suggests that Lidocaine concentration has effects against Streptococcus mutans bacteria in the concentrations of 2%, 1% and 0.5%, to inhibit bacterial growth (p<0.05), but there was no bacteriocidal potential of Lidocaine concentration against Streptococcus mutans bacteria (p>0.05).